Analisis Dampak Strategi Pengembangan Ekonomi: Studi Kasus Indonesia Dan Singapura - Agustanta, Nainta; Oktafiona, Agnes; Nur'aini, Nisrina Hani; Ghifari, Jamaludin Al (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2024)
The progression of globalization demands that each country adopt adaptive and competitive economic strategies. This article compares the economic strategies of Indonesia and Singapore, two countries with distinct characteristics. Indonesia, as a developing country, emphasizes decentralization, human resource development, structural transformation, and equitable development. In contrast, Singapore focuses on industrialization, service sector development, technological innovation, and the promotion of free markets and foreign investment. The method used is a literature review by analyzing secondary data from various sources. The findings reveal significant differences in economic systems, population size, and development approaches. Despite limited natural resources, Singapore has achieved a high level of economic development, while Indonesia continues to face challenges related to inequality and economic vulnerability. This comparison is expected to serve as a reference for Indonesia in formulating sustainable and globally responsive economic strategies.